Influence of Resource Influence the Implementation of the County Integrated Development Plan of Kisii County, Kenya - Geoffrey Mokua Abuga,; Dr. Simon Nyakwara, (IJRDO - Journal of Business Management, 2020)
In Kenya, the county Governments are required by planning and budgeting guidelines (URT, 2011) to have five years strategic plans (CIDP) which all the counties comply. However, its implementation is always not effective.  In Kisii County, CIDP implementation seam not effective as per audit reports for four consecutive years from the controller and auditor general for financial year 2013/2014; 2014/2015; 2015/2016 and 2016/2017 which shows that most of the funds planned for projects were diverted. It is for this reason that this study wished to assess the factors influencing the implementation of County Integrated Development Plan in Kisii County-Kenya. The study adopted a descriptive survey research design. The study chose this research design because the study aimed at collecting information from respondents on their attitudes and opinions in relation to factors influences the implementation of strategic plans in County Government. The study targeted the members of the county Government, Chief executive officers, chief offices, about 3,000 staff of the county from various sections, stakeholders (contractors, chambers of commerce, NGO council members and the citizen of Kisii. The sample size of 384 respondents was determined using the Fisher et al., (1998) formulae. MCA, CEC and chief officers were purposively sampled while other county staff and stakeholders were Stratified then randomly sampled. Interviewer administered questionnaires were used as a data collection tool. Quantitative data was analyzed using descriptive statistics and presented data in tables. The study established that top leadership influenced operations in the county government yet they lacked strategies to facilitate employee’s performance; there was no enough skilled staff to implement the CIDP; the resource were always not availability for the implementation of the CIDP. Culture of Corruption, Politicizing every development initiative, culture of Tribalism and Nepotism had contributed to ineffective implementation of CIDP. There was delay in Stages and process, not restricted to the prioritized projects and no review of plans to ensure effective implementation of projects and services as prioritized in the CIDP. Correlation analysis revealed that leadership support, resources, organization culture and stakeholder involvement positively and significantly influence the implementation of CIDP.